Varieties of Populism across a Left‐Right Spectrum: The Case of the Front National, the Northern League, Podemos and Five Star Movement. Issue 4 (31st October 2017) - Ivaldi, Gilles; Lanzone, Maria Elisabetta; Woods, Dwayne
Abstract: This article engages in a comparative analysis of populist parties across the West‐European left‐right spectrum. Conceptualizing populism as a 'thin ideology', we argue that populist parties show both similarities and differences, and that these are a product of the interaction of the core features of populism with the 'thicker' ideological traditions from which the different parties draw upon. We employ a qualitative method in analyzing the core ideational features of populism in four different populist parties, both left and right. We find that all four parties converge in particular on their conception of the elite as a separate 'caste', in relation to economic and European integration conflicts, operating on patriotism and in claiming that they represent the true interests of the sovereign people. They differ, however, in their conception of the 'true' people that they presumably represent and the nature of popular sovereignty and populist democracy.